USTIFICATION OF THE APPLICATION OF OXYGEN ELECTRODE COMPARISON WITH β-Al2O3 MEMBRANE IN TUNGSTEN-MOLYBDATE MELTS - Malyshev, Victor; Nesterenko, Tetiana; Shakhnin, Dmytro; Gab, Angelina; Volyar, Roman (Scientific Journal "Metallurgy", 2024)
Four conditions for using the electrode system as a reference electrode are formulated: compliance of the electrode system with the type of measurements; inertness of electrode system materials; stability and reproducibility of potential values; reversibility of the electrode system. Taking into account the physicochemical properties of tungstate-molybdate systems, melts based on sodium tungstate and chloride tungstate-(molybdate)-containing melts were selected as electrolytes for comparison electrodes. As a membrane of the reference electrode, a material based on β-Al2O3 (Na2O⋅11 Al2O3) was used. The stability of this material in both acidic and basic melts has been proven. The temperature limits for the use of this material as a membrane have been determined experimentally: 723-1073 K. It is assumed that the potential of a platinum-oxygen electrode with a membrane on the base of β-Al2O3 is determined by the partial pressure of oxygen in the atmosphere inside the membrane tube. Calculated values of the diffusion potentials on the porous diaphragm. They do not exceed 3⋅10-3 V. Diffusion potentials reach a stationary value within several minutes. The potential of the oxygen electrode relative to the reference electrode will be determined by the ratio of О2- ion activities in the investigated melt and in the melt of the reference electrode. To check the reversibility of the proposed system, the study of electrochemical equilibrium on platinum electrodes and their micropolarization studies were conducted. The absence of hysteresis on the micropolarization curves proves the reversibility of the proposed electrode system. The stability and reproducibility of potential values have been experimentally proven. The use of a comparison oxygen electrode with a β-Al2O3 membrane in melts containing compounds of carbon, boron, silicon, molybdenum, and tungsten will allow for a more reasonable solution to the issue of controlling and combining the potentials of the electroreduction processes of these compounds. The latter will make it possible to practically implement the technology of high-temperature electrochemical synthesis of carbides, borides and silicides of molybdenum and tungsten in molten salts.